İlk kez hastaneye yatan okul çağı çocukların hemşireyi algılayışları - Tarakçı, Sevim (My University, 2001)
Çocuk ve hemşire arasındaki ilk ilişki hasta çocuğun herhangi bir sağlık kurumuna kabulü ile başlar. Hastanede yattığı süre içinde daha yoğunlaşarak devam eder. Hastaneden taburcu olurken, evde bakımında ve kontrollerinin yapıldığı dönemde de ilişki sürer. Araştırma, Akdeniz Üniversitesi Tıp Fakültesi Hastanesi Çocuk Sağlığı ve Hastalıkları Kliniğinde, ilk kez hastaneye yatan, okul çağı çocuklarının hemşireyi algılayışlarını ve algılamayı etkileyen faktörleri değerlendirmek amacıyla 40 çocuk ve annesiyle yapılan tanımlayıcı ve deneysel bir araştırmadır. Veriler araştırıcı tarafından ilgili literatür bilgilerinden derlenerek Anket Formu ile toplanmıştır. Çocuğun hemşireyi algılayışını ifade edebilmesi için ise hastanede bir hemşire, doktor ve hasta çocuğu içeren resim çizimleri yaptırılmıştır. Verilerin değerlendirilmesinde, yüzde dağılımı ve çizdirilen resimlerde ise bu konuda uzman kişilerin yorumları kullanılmıştır. Çocukların %55'i erkek, %50'si 8-9 yaşları arasında, %22.5'inin hastaneye yatma nedenleri kusma, karın ağrısı, ateş olduğu görülmüştür. Hastanedeki çocukların % 80'inin paylaşımları olduğu ve %70'inin yaşıtlarıyla oyun odasında oynadığı belirlenmiştir. Çocukların çoğunluğu (%82.5)yaşamlarında hemşire ile ilk kez okulda aşılama programlarında karşılaşmışlardır. Çalışmanın yapıldığı klinikte ise %35'i hasta kabulünde, %30'u odadaki diğer hastaya yapılan uygulamada ve %27.5'i hemşirenin ona ilk uygulama yaptığında karşılaştığı belirlenmiştir. Çocukların %65'i gelecekte hemşire olmak istemediklerini ve istememe nedeni olarak ta %46.1'i kız olmadığını, %30.7'si zor meslek olduğunu belirtmişlerdir. Hemşirelik Mesleği kadın mesleği ve zor meslek olarak algılanmaktadır. Çocuklar hemşirelerin hastanedeki işlevlerini, %100'ü ateş, nabız, tansiyon ölçmek, enjeksiyon yapmak ve ilaç vermek olarak değerlendirmişlerdir. Çocukların % 57.5'inin hemşirelerin fiziksel işlevlerinden dolayı, çocukların canını acıttığını düşündükleri saptanmıştır. Çocukların %82.5'i klinikte sevdiği hemşirenin olduğunu ve hemşire / hemşireleri sevme nedenlerini çocuklar ile ilgilenmesi (%100) ve hiç kimseye kızmaması (%90.9) olduğu belirlenmişlerdir. Hemşireleri sevmeme nedenleri, sevme nedenleri ile paralellik gösterip çocuklara kızması (% 100), onlar ile ilgilenmemesi (% 71.4), anneler çağırınca gelmemesi (%57.1) olduğu görülmektedir. Sonuç olarak, çocuğun hemşireyi yakından gözlediği, hemşirenin işlevlerini belirleyebildiği ve olumlu / olumsuz duygularla bağlı olarak algıladığı hemşireyi yaptığı resimlere yansıttığını söyleyebiliriz.

HOW THE SCHOLL AGE KIDS WHO ARE UNDERTREATMENT FIRST TIME PERCENE THE NURSE The first relationship between the child and the nurse begins when the sick child steps in the hospital and that relationship is perpetuated in a trend of increasing density in the course of child's stay at the hospital. It is maintained even after child checing out of the hospital, at his o r her home treatment and at times of periodic controls. The research which has been carried out by the Department of Pediatric health and Illness of the Faculty of Medicine at Mediterranean University has been made for the analysis of the perception of School Aged Children towards the nurse and that of those perception-determining factors involving 40 kids and their mothers which has rather been a complementary and experimental research. All the data collected by research analysts has been made up of relevant information by virtue of questionnaire forms and picture drawings. Such drawings were made by children in the forms of the nurse, doctors and sick infants so as to ellicit child's conception of the nurse. The over all analysis of the data has been made in percantage terms and that of expert intrepretations have been made use of. It was noted that 55 % of children was male and that 50 % was between ages of eight and nine and that 22.5 % of children was initially gone to hostipal for the reasons of vomiting, stomach ache and fever. It was also stated that 80 % of children at the hospital enjoyed sharing with other children and that 70 % played with the same age group in the playing chambers. The majority of kids (82.5 %) was initially introduced to nurses at the scholl vaccination programmes first time in their lives whilst 35 % at the clinic where the research was made encountered them at patient reception. 30 % met them at the chambers where other patients were treated and 27.5 % came accross them when they were first treated. 65 % of kids clearly stated that they had not wished to became nurse themselves due to the fact that they had not been born as females corresponding to 46.1 % of kids whilst about 30.7 % states that it was a difficult profession itself. Almost children (%100) regarded nurse jobs at hospitals as measuring temperatures, taking pulse rates, blood pressures, giving shots and medications. It has been revealed that about 57.5 % of children considered nurses hurting them physically merely because of their physical activieties and responsibilities. About 82.5 % of those children states that they had nurses at the clinic whom they liked and that was caused by their friendly concerns for children (%100) and that they never exhibited anger or bad tempers to anyone. As for the reasons why they did not like nurses showed almost 100 % thought of nurses as getting angry with them and that about 71.4 % indicated their insufficient concerns for them and that they did not respond to call of mothers (57.1 %). The majority of children's picture drawings corresponding to 62.5 % revealed that doctors and nurses were perceived positive, kind, affectionate and considered. In conclusion me may point out the perception of kids primarily for the nurse is well reflected in the drawings they made exhibiting certain clues whether children like or dislek them.
Keywords: Çocuk Hastalıkları Hemşireliği